Effectiveness of Styrax Paralleloneurus Extract as Anti-Inflammatory Agent on Incision Wounds in Male White Mice (Mus Musculus) - Meriani Herlina; Noradina Noradina; Bernita Silalahi; Ratna Dewi; Syahrul Handoko Nainggolan; Ali Asman; Ririn Mariska Sitanggang (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
Incision wounds are characterized by tissue damage or loss caused by sharp objects. Inflammation is the body's protective response to infection, irritation, or injury, marked by redness, heat, swelling, pain, and tissue dysfunction. Styrax paralleloneurus resin has potential wound-healing properties. This study aimed to investigate the anti-inflammatory effects of Styrax paralleloneurus extract on incision wounds in male white mice. Twenty-five mice were divided into five groups: positive control (Betadin), negative control (Vaseline), and three groups receiving 5%, 10%, and 15% Styrax paralleloneurus extract concentrations. Incision wounds (1cm x 0.2cm) were created on the dorsal area. Wound length and closure were observed daily using calipers. ANOVA analysis revealed significant differences (p=0.138 > 0.05) among the extract concentrations, indicating a concentration-dependent anti-inflammatory effect. The 15% concentration demonstrated the fastest wound healing. Bioactive compounds, such as flavonoids, saponins, and terpenoids, likely contribute to the anti-inflammatory effects. This study supports previous research on Styrax paralleloneurus' wound-healing properties. The results suggest Styrax paralleloneurus extract as a potential phytotherapeutic agent for wound healing. Further clinical trials and stability testing are recommended to develop a phytopharmaceutical product. Future studies should investigate the extract's mechanism of action and potential interactions with other medications. Conclusion The 15% concentration of Styrax paralleloneurus extract exhibited the fastest anti-inflammatory effects on incision wounds in male white mice.Recommendations: Conduct clinical trials to assess the stability, efficacy, and safety of Styrax paralleloneurus extract for phytopharmaceutical product development.